SYSTEMATIC LITERATUR REVIEW: Kemampuan Koneksi Matematika Berdasarkan Self Confidence - Marda’ Ulya Reksadini; St. Budi Waluya; Mohammad Asikin; Zaenuri (Civiliza Publishing, 2021)
Various things from previous research studies have been attempted to build mathematical connections and their uses from various types of indicators of mathematical connections and a sense of self-confidence. So the purpose of this study is to classify the types of mathematical connections and students' self-confidence. The method used in this study is the SLR (Systematic Literature Review) method. This study is intended to gain the strength of scientific studies in building a framework of mathematical connection abilities through the types of indicators of mathematical connections that suit the needs and identify self-confidence. The results of the study of several articles on the types of mathematical connections, to build mathematical connection skills, in this study recommend four types of mathematical connections of students, namely: (1) connecting between concepts in one mathematical material, (2) connecting between concepts in the field of mathematics, (3) connecting mathematical concepts with other fields, and (4) connecting mathematical concepts to solve problems in everyday life. Based on the results and discussions that have been described, it can be concluded that self-confidence has a significant effect on students' mathematical connection abilities, so that students' self-confidence has a positive effect on students' mathematical connection abilities.